Adolescents' Participation in School Physical Activity before and during the COVID-19 Pandemic: An Educational Priority - Karel Frömel; Dorota Groffik; Josef Mitáš (MDPI AG, 2023)
The aim of this study was to identify the structure of weekly physical activity (PA) of adolescents with varying degrees of participation in school PA and motivation for PA before and during the COVID-19 pandemic. PA was assessed using the IPAQ-long form and motivation by using the MPAM-R questionnaire. Participants (N = 1257) were divided into groups involved and not involved in school PA. During the pandemic, the greatest decrease was observed in vigorous and moderate PA in boys (H = 98.52, p < 0.001, η2 = 0.179) and girls (H = 56.86, p < 0.001, η2 = 0.075) involved in school PA and in boys involved and not involved in school PA and in transportation PA. Physical education (PE) teachers should focus on promoting vigorous PA and home PA for boys and girls in the post-pandemic period. Student participation in school PA and an increase in overall PA should be supported through distance PE, which should be a mandatory part of PE programs and comprehensive school PA programs.